2020
DOI: 10.2337/dc19-1902
|View full text |Cite|
|
Sign up to set email alerts
|

Coronary Artery Disease and Type 2 Diabetes: A Proteomic Study

Abstract: Coronary artery disease (CAD) is a major challenge in patients with type 2 diabetes (T2D). Coronary computed tomography angiography (CCTA) provides a detailed anatomic map of the coronary circulation. Proteomics are increasingly used to improve diagnostic and therapeutic algorithms. We hypothesized that the protein panel is differentially associated with T2D and CAD. RESEARCH DESIGN AND METHODSIn CAPIRE (Coronary Atherosclerosis in Outlier Subjects: Protective and Novel Individual Risk Factors Evaluationda coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 38 publications
1
36
0
2
Order By: Relevance
“…And increased concentrations of renin and growth differentiation factor 15 (GDF15) proteins and a lower adiponectin level were independently associated with coronary heart disease and diabetes mellitus [31]. In a proteomic study of Monu with co-authors, differences in 19 proteins were identified in the blood of patients with coronary heart disease compared to healthy ones.…”
Section: Results Of Proteomic Blood Tests In Population Groups Of Individuals and Non-complicated Coronary Heart Diseasementioning
confidence: 99%
“…And increased concentrations of renin and growth differentiation factor 15 (GDF15) proteins and a lower adiponectin level were independently associated with coronary heart disease and diabetes mellitus [31]. In a proteomic study of Monu with co-authors, differences in 19 proteins were identified in the blood of patients with coronary heart disease compared to healthy ones.…”
Section: Results Of Proteomic Blood Tests In Population Groups Of Individuals and Non-complicated Coronary Heart Diseasementioning
confidence: 99%
“…The use of omic disciplines-globally referred to as panomic or multi-omic technologies-to support decisional processes may represent a daunting perspective for clinicians dealing with ischaemic heart diseases. Only recently have paradigms begun to shift, with big data collection starting to offer omic information to practicing cardiologists [17][18][19]. On the other hand, oncology, haematology, immunology and infectious diseases have been integrating these tools for some decades into what are now wellestablished diagnostic and treatment protocols [12].…”
Section: Current Precision Treatments Of Acute Coronary Syndromesmentioning
confidence: 99%
“…Only one of these studies showed a modest improvement in discrimination by adding 3 proteins (MASP, ApoE, and CRP) to the standard clinical model (AUC increased from 0.75 to 0.77). Up to 142 plasma proteins have been associated with prevalent T2D [ 59 •, 60 , 61 ] in cross-sectional studies, which aim to identify differences between T2D patients and well-matched control samples or associations with glycaemic parameters, providing a cost-effective and simple prioritisation strategy. However, these studies suffer from reverse confounding, i.e.…”
Section: Existing Strategies For T2d Prediction Screening and Diagnmentioning
confidence: 99%